The frequency of the rhetorical pattern of undergraduate thesis background section in English education departments of two universities in Aceh - Imam Al Farisyi; Iskandar Abdul Samad; Saiful Marhaban (Universitas Syiah Kuala, 2022)
This research examined the rhetorical pattern of thesis background, particularly the undergraduate scripts of English education department students. The study aims to find out the frequency of the rhetorical patterns in writing thesis background. The approach used in this study is a qualitative method based on content analysis. The sample consisted of 20 English education undergraduate theses from two universities in Indonesia. The data were analyzed based on Kanoksilapatham (2005) classification by following the framework of Swales’s CARS model (2004). The results show that the undergraduate students of English departments have a similar frequency of the rhetorical pattern with the framework guidance. Although some students have reached an adequate standard in writing research background using their own way, they also should improve the language style in academic writing.